Medium-term Impact of Organic and Microbial Fertilization on Production Efficiency and Fertility of Soil in an Apple Production System under North West Himalayan Region. Issue 3 (4th February 2022) - Kumar, Sarvendra; Sharma, Anil; K.G., Rosin; Sharma, Vinod K.; Sinha, Subodh K.; Kumar, Dinesh; Dwivedi, Neeta; ., Vishwanath
ABSTRACT: Continued exhaustive use of chemical fertilizers and environmental changes led to a decline in soil fertility and production efficiency, which eventually results in land degradation. The application of beneficial microorganisms and organic fertilizer may be an effective measure for sustainable agriculture production. Thus, a field experiment was conducted to investigate the impact of mineral and organic fertilizers (vermicompost/farm yard manure) supplemented with microbial inoculants on growth and soil health parameters of apple ( Malus domestica cv. Oregon Spur) under medium density (4 m × 4 m) plantation. Nine integrated treatments of different combination of organic, inorganic and microbial inoculants were studied with four replications. Results revealed that plants received 75% of recommended (RD) NPK + Azospirillium had maximum increase in trunk cross section area (TCSA) and canopy volume (14.3 and 19.3%, respectively), average fruit yield (17.1 t ha −1 ) and production efficiency (0.92 g cm −2 TCSA) of apple during experiment period (2012–2015). Continuous 3 years of organic fertilization and microbial inoculants enhanced nutrient status of soil. Microbial biomass carbon, N and dehydrogenase activity of soil increased by 37%, 48% and 76%, respectively, in 50% of RD NPK + 25% N through FYM + 25% N through VC over control. Deviation from optimum percentage (DOP) index revealed 50% substitution of inorganic to organic fertilization (FYM and VC) is appropriate to correct deficiency of primary and secondary nutrients in leaves. Canonical correlation analysis revealed yield of apple was negatively correlated with DOP indices. In conclusion, 50% of inorganic fertilizers substituted through VC and FYM, and 25% inorganic fertilizers substituted through inoculation of Azospirillium, resulted higher fruit yield of apple in north west Himalayan region.